Improving Logical Thinking Skills through Sorting Box Games for 5-6 Years Old Children at Ra Ar Raudhah Ganjuran - Kholifah, Ida; Darniati (Jurnal Profesi Guru Indonesia, 2025)
This study aims to improve logical thinking skills through sorting box games in children aged 5-6 years at RA Ar Raudhah. Based on the background of the problem, namely the problem in the material of introducing geometric shapes and grouping geometric shapes has not been optimal because the media used is less varied and interesting for children. then a problem can be formulated, namely How to improve logical thinking skills through sorting box games in children aged 5-6 years at RA Ar Raudhah? and Can this sorting box game improve the logical thinking of children aged 5-6 years? This study is a classroom action research with the research subjects being the data of children at RA AR RAUDHAH group B totaling 12 children, consisting of 4 sons and 8 daughters. The purpose of this learning research is "to improve logical thinking skills through sorting box games in children aged 5-6 years at RA Ar Raudhah. Data collection methods use interviews, observations, work results and documentation. Data analysis techniques use quantitative percentages and qualitative. The conclusion of the results of this study is that with the activity of recognizing geometric shapes, matching geometric shapes according to their pattern shapes and classifying or grouping geometric shapes according to their groups using a sorting box has increased. This can be proven by looking at the achievement of children's logical thinking skills as follows in cycle 1 children who are able to recognize geometric shapes reach 33.33% pairing geometric shapes reaches 33.33% and grouping geometric shapes reaches 33.33% and in cycle 2 in recognizing geometric shapes reaches 91.66%, matching geometric shapes reaches 86.33% and grouping geometric shapes reaches 86.33%. From the results of the classroom action research carried out, it shows that the sorting box is an effective medium for improving logical thinking skills in children aged 5-6 years at RA Ar Raudhah.